The wisdom of eccentric old men : a study of type and secondary character in Galdós's social novels, 1870-1897 - Bly, Peter (McGill-Queen's University Press, 2004)
"In The Wisdom of Eccentric Old Men Peter Bly reveals that Benito Perez Galdos deliberately and consistently employed eccentric older gentlemen, a not-uncommon secondary character type, to emphasize the significance of major plot developments and to underline the strengths or weaknesses of principal characters."--Jacket.